GR-RNF43 Regulation in Colorectal Cancer - Ertugrul, Dalgic; Irene, Li; Aritro, Nath; Christina, Chan (Journal of Proteomics and Genomics Research, 2016)
In contrast to approaches that compare pair-wise control (i.e. normal) to treated (i.e. disease) samples, we compared colorectal cancer samples not only to a set of control samples but also against a wide range of samples and conditions to collect the differentially expressed genes and identify target genes. We identified specific genes for colorectal cancer and showed that they are significantly associated with colorectal cancer in the literature. Analysis of independent datasets revealed a significantly distinct expression pattern for glucocorticoid receptor (GR) and ring finger protein 43 (RNF43) in colorectal cancer samples. GR was downregulated whereas RNF43 was upregulated in colorectal cancer with respect to various conditions in different datasets. In HCT116 colorectal cancer cell line, knock-down of GR levels with siRNA resulted in increased RNF43 levels, suggesting that GR might be a negative regulator of RNF43. Our study suggests that the downregulation of GR might be involved in the upregulation of RNF43 in colorectal cancer.
Keywords: Functional genomics; computational biology; colorectal cancer; differential expression.